The Role of Bacterial Biofilms in The Formation of Recurrent Adenoiditis and Sinusitis in Children - Madaminova N.E.; Saliakhunova Kh.O.; Kosimov Kh.K.; Rakhimov S.K. (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
Background. Recurrent adenoiditis and sinusitis in children remain a significant challenge in pediatrics due to increasing pathogen resistance. This study aimed to investigate the impact of bacterial biofilms on inflammation chronicity and to find ways to improve conservative therapy outcomes at the Andijan State Medical Institute clinic. Methods. The study included 84 patients (aged 3–12 years) with verified recurrent adenoiditis and chronic sinusitis. Along with standard endoscopic and CT examinations, a microbiological analysis of adenoid vegetation fragments (n=32) was performed using biofilm extracellular matrix detection methods. Statistical analysis was carried out using Student's t-test. Results. Polymicrobial associations organized into biofilms were identified in 68% of children, which correlated with the low effectiveness of standard antibiotic therapy (22.8% efficiency in the biofilm group vs. 74.1% in the control group). It was established that adenoid biofilms provoke the development of otitis media with effusion in 43.8% of cases, creating an infection reservoir inaccessible to conventional doses of systemic drugs. Conclusions. The presence of bacterial biofilms is a determining factor in the recurrence of ENT pathologies in children. The findings justify a shift from massive antibiotic therapy to a strategy of biomatrix destruction and topical sanitation. This approach helps reduce the frequency of unjustified adenotomies and decreases the drug load on the child's body.